Stochastic Processes and Their Applications: In Honor of Prof. Sally McClean - P.-C. G. Vassiliou; Andreas C. Georgiou (Mathematics)
Stochastic processes are foundational tools in many scientific disciplines, including biology, operational research, social sciences, and stochastic finance, among others [...]